2016
DOI: 10.1111/bjh.14099
|View full text |Cite
|
Sign up to set email alerts
|

Increased iron stores prolong the QT interval – a general population study including 20 261 individuals and meta‐analysis of thalassaemia major

Abstract: The prolongation of cardiac repolarization (QT interval) has been investigated in studies of patients with secondary iron overload. However, no previous population-based study examining the effect of increased iron stores on QT interval prolongation has previously been undertaken. We tested the hypothesis that increased iron stores and haemochromatosis genotype (genetically increased iron stores) are associated with prolongation of the QT interval. We included 20 261 individuals from the Danish General Suburba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 48 publications
0
7
2
Order By: Relevance
“…QTc interval is reasonably specific to diagnose iron overload cardiomyopathy. Previous studies revealed that increasing iron stores in men correlated with prolonged QTc interval and may induce cardiac arrhythmias, including torsades de pointes, ventricular fibrillation, and sudden cardiac death [25,26]. We found no significant differences in QT and QTc intervals between ferritin groups nor between MR-T2 � groups.…”
Section: Plos Onecontrasting
confidence: 70%
“…QTc interval is reasonably specific to diagnose iron overload cardiomyopathy. Previous studies revealed that increasing iron stores in men correlated with prolonged QTc interval and may induce cardiac arrhythmias, including torsades de pointes, ventricular fibrillation, and sudden cardiac death [25,26]. We found no significant differences in QT and QTc intervals between ferritin groups nor between MR-T2 � groups.…”
Section: Plos Onecontrasting
confidence: 70%
“…To function as the control group without diabetes mellitus, participants were included from the Danish General Suburban Population Study (GESUS), which included participants between 2010–2013 aged 20 years or older ; 8823 participants had a digital ECG on file. Cases and controls were matched by age and gender, and two controls were matched for each case.…”
Section: Participants and Methodsmentioning
confidence: 99%
“…Overall, 19 405 people were included in this study. Details about the GESUS study design have previously been described …”
Section: Methodsmentioning
confidence: 99%